Integrated Methylome and Transcriptome Analysis Widen the Knowledge of Cytoplasmic Male Sterility in Cotton (Gossypium barbadense L.) - You, Jingyi; Li, Min; Li, Hongwei; Bai, Yulin; Zhu, Xuan; Kong, Xiangjun; Chen, Xiaoyan; Zhou, Ruiyang (Frontiers in Plant Science, 2022)
DNA methylation is defined as a conserved epigenetic modification mechanism that plays a key role in maintaining normal gene expression without altering the DNA sequence. Several studies have reported that altered methylation patterns were associated with male sterility in some plants such as rice and wheat, but global methylation profiles and their possible roles in cytoplasmic male sterility (CMS) , especially in cotton near-isogenic lines remain unclear. In this study, bisulfite sequencing technology and RNA-Seq were used to investigate CMS line 07-113A and its near-isogenic line 07-113B . Using integrated methylome and transcriptome analyses, we found that the number of hypermethylated genes in the differentially methylated regions, whether in the promoter region or in the genomic region, was more in 07-113A than the number in 07-113B. The data indicated that 07-113A was more susceptible to methylation. In order to further analyze the regulatory network of male sterility, transcriptome sequencing and DNA methylation group data were used to compare the characteristics of near-isogenic lines 07-113A and 07-113B in cotton during the abortion stage. Combined methylation and transcriptome analysis showed that differentially expressed methylated genes were mainly concentrated in vital metabolic pathways including the starch and sucrose metabolism pathways and galactose metabolism. And there was a negative correlation between gene methylation and gene expression. In addition, five key genes that may be associated with CMS in cotton were identified. These data will support further understanding of the effect of DNA methylation on gene expression and their potential roles in cotton CMS.